Noradrenaline and mixed alpha(2)-adrenoceptor/imidazoline-receptor ligands: effects on sodium intake - Sugawara, A. M.; Miguel, T. T.; de Oliveira, L. B.; Menani, José Vanderlei [UNESP]; De Luca, L. A. (Elsevier B.V., 1999)
The effect of noradrenaline, and mixed ligands to alpha(2)-adrenoceptors (alpha(2)-AR) and imidazoline receptors (IR), injected intracerebroventricularly (i.c.v.), on sodium intake of sodium depleted rats, was tested against idazoxan, a mixed antagonist ligand to alpha(2)-AR and IR. The inhibition of sodium intake induced by noradrenaline (80 nmol) was completely reversed by idazoxan (160 and 320 nmol) injected i.c.v. The inhibition of sodium intake induced by mixed ligands to alpha(2)-AR and IR, UK14,304, guanabenz and moxonidine, was antagonized from 50 to 60% by idazoxan i.c.v. The results demonstrate that noradrenaline, a non-ligand for IR, acts on alpha(2)-AR inhibiting sodium intake. The possibility that either alpha(2)-AR or IR mediate the effect of mixed agonists on sodium intake remains an open question. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: adrenergic; imidazoline; sodium appetite; water intake; dehydration